'48 - Herbert, James, 1943-2013 (London HarperCollins, 1996)
In 1945, Hitler unleashes the Blood Death on Britain as his final act of vengeance. Hoke, an American pilot and one of a tiny minority with a rare blood group unaffected by the deadly disease, has survived alone among the debris and the dead of London for three years. Now, in 1948, a slow-dying group of Fascist Blackshirts believe their only hope is a transfusion of blood from one of Hoke's kind. Ever more desperate as their deaths approach, they're after his blood
Keywords: England--London -- Plague -- World War (1939-1945)